Nomeação e associação semântica na doença de alzheimer e no envelhecimento típico em função da escolaridade - Gonçalves, Ariane Treges Noronha (2021)
The increase in human life expectancy has influenced research worldwide, leading to the development of studies focusing on cognition and aging. Investigating possible declines in language and memory is essential for the early diagnosis of neurodegenerative diseases, such as Alzheimer’s Disease (AD). The administration of semantic association and picture naming tasks may bring evidence of cognitive decline associated to AD, and studies have sought to find more conclusive evidence about the impact of psycholinguistic criteria (such as frequency and animacity) as well as of schooling in these types of processing. This dissertation aimed at analyzing how the process of picture naming and semantic association occurs in the comparison between typical older adults as a function of schooling (Study 1) and between typical older adults and a group of older adults diagnosed with mild AD (Study 2), taking into account psycholinguistic criteria as well as types of semantic associations. In Study 1, the participants were 46 typical older adults with high schooling (age 65-80 years old, m=70.22, sd=4.69, schooling 9 or more, m=14.93, sd=2.79), and 44 older adults with low schooling (age 65-80 years old, m=72,20, sd=4,65, schooling 2-8 years of formal study, m=4.95, sd=2.01). The results of the picture naming task indicated that more schooled participants were more accurate in high frequency and nonliving items, as compared to the low-schooling group. In the semantic association tasks, participants were more accurate in nonliving items than living ones, regardless of schooling level, while the type of association did not distinguish the groups. Study 2 was developed with 13 typical older adults (age 65-80 years old, m=72.92, sd=5.33, schooling 2-8 years of formal education, m=5.08, sd=2.06) and 13 older adults diagnosed with mild AD (age 65-80 years old, m=75.92, sd=4.75, schooling 2-8 years of formal education, m=6.08, sd=1.97), both groups with low schooling. In both studies, the participants performed a picture naming and a semantic association task. The results of the picture naming task showed that the interaction “frequency” versus “group” was significant only for the typical aging group (p<0.05). The interaction “frequency” versus “animacity” was significant (p<0.05) in both animate and inanimate stimuli, indicating that both groups obtained better results in naming high frequency inanimate objects as compared to animate and low frequency items. In the semantic association task, the results of the mixed effects showed that the group effect (p<0.05) and the effect of animacity (p<0.05) were significant, but there were no differences regarding the type of association. The studies indicate the efficiency of the analyses of psycholinguistic criteria and of schooling in the 10 assessment of linguistic processing in typical aging and in AD with the use of naming and semantic association tasks.